Real-world survival outcomes of wedge resection versus lobectomy for cT1a/b cN0 cM0 non-small cell lung cancer: a single center retrospective analysis - Bertolaccini, Luca; Cara, Andrea; Chiari, Matteo; Diotti, Cristina; Glick, Nimrod; Mohamed, Shehab; Uslenghi, Clarissa; Mazzella, Antonio; Brambilla, Daniela; Bertolotti, Raffaella; Sedda, Giulia; Spaggiari, Lorenzo (Frontiers in Oncology, 2023)
BACKGROUND. JCOG0802/WJOG4607L showed benefits in overall survival (OS) of segmentectomy.CALGB 140503 confirmed that sublobar resection was not inferior to lobectomy concerning recurrence-free survival (RFS) but did not provide specific OS and RFS according to the techniques of sublobar resections. Hence, we retrospectively analyze the survival differences between wedge resection and lobectomies for stage IA lung cancer.We reviewed the clinical records of patients with clinical stage IA NSCLC over 20 years.The inclusion criteria were: preoperative staging with CT scan and whole body CT/PET; tumor size <20 mm; wedge resections or lobectomies with or without lymph node dissection; NSCLC as the only primary tumor during the follow-up period. We excluded: multiple invasive lung cancer; positive resection margin; preoperative evidence of nodal disease; distant metastasis at presentation; followup time <5 years. The reverse Kaplan -Meier method estimated the median OS and PFS and compared them by the log-rank test. The stratified backward stepwise Cox regression model was employed for multivariable survival analyses.. 539 patients were identified: 476 (88.3%) lobectomies and 63 (11.7%) wedge resections.The median OS time for the whole cohort was 189.7 months (range: 173.7 -213.9 months). The 5year wedge resection and lobectomy OS were 82.2% and 87.0%. The 5-year RFS of wedge resection and lobectomy were 17.8% and 28.9%. The log-rank test showed no significant differences (p = 0.39) between wedge resections and lobectomies regarding OS and RFS (p = 0.23).Lobectomy and wedge resection are equivalent oncologic treatments for individuals with cN0/cM0 stage IA NSCLC <20 mm. Validating the current findings requires a prospective, randomized comparison between wedge resection and standard lobectomy to establish the prognostic significance of wedge resection.